Bibliometric Analysis of Global Research on Long-Acting Reversible Contraception and Healthcare Workers - Jusoh, Nur Nabila; Tengku Ismail, Tengku Alina (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Long-acting reversible contraception (LARC) is a feasible solution to reduce unintended pregnancy and abortion rates. Nonetheless, the worldwide prevalence of LARC remains low. The LARC uptake depends heavily on healthcare workers because every LARC insertion requires a clinician’s visit, and they are a trusted source of contraceptive information. The study is aimed to explore the trend and distributions of global publications related to LARC and healthcare workers. MATERIALS AND METHODS: Articles related to LARC and healthcare workers were retrieved from the Scopus database. Eligible publications were limited to research articles, reviews, and conference papers published in the English language with no date restriction. The bibliometric data was analysed using Biblioshiny to obtain distributions in terms of the number of publications, journals, countries, institutions, citations, and keywords. RESULTS: A total of 681 eligible publications related to LARC and healthcare workers were retrieved from the Scopus database between 1967 to 2022. The number of publications was low for the first four decades but increased steadily from 2010 onwards. The leading country in this research area was the United States of America and the majority of the most productive institutions were from this country. Half of the frequently cited publications highlighted healthcare workers’ bias, attitude, and practice on LARC provision to clients. CONCLUSION: This bibliometric analysis can guide scholars to understand the global overview of research about LARC and healthcare workers. It may be useful for health practitioners and researchers who are interested in exploring this research area.